Luftnot, Husten und Tachykardie - Eichhorn, Florian; Heußel, Claus Peter; Storz, Konstantina; Dreher, Sascha; Dienemann, Hendrik (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2012)
Pneumopericardium is known as a rare complication following cardiothoracic surgery or intravenous line placement. Baseline examination including chest x-ray may lead to diagnosis. To prevent cardiac tamponade, pericardiotomy or adaequate pericardial drainage is crucial. We revealed pneumopericardium as the reason for new dyspnea and tachycardia in a 56-year-old man 3 weeks after lobectomy and lymphadenectomy because of a non-small cell lung cancer. Early decision for transpleural pericardiotomy prevented a possibly lethal course.
Gesehen am 27.06.2019